The The effect of insecticide application on Arthropod communities in sugarcane plantations - Asmoro, Prayogo Probo; Sari, Lidia; Munif, Abdul (JURNAL AGRONIDA, 2025)
This study aimed to evaluate the effects of biological insecticides (Bacillus thuringiensis and Bacillus siamensis) and chemical insecticides (Carbofuran and Chlorantraniliprole) on the diversity, abundance, and community structure of arthropods in sugarcane (Saccharum officinarum L.) plantations. The research compared species richness, diversity indices (Shannon-Wiener, Simpson, Evenness), and functional composition of arthropods across plots treated with biological insecticides, chemical insecticides, and untreated controls. Results showed that biological insecticides significantly maintained or enhanced species richness (65–67 species) and individual abundance (945–996 individuals) compared to chemical insecticides (44–47 species; 514–783 individuals). The highest Shannon-Wiener diversity indices were observed in biological treatments, indicating a more balanced and stable arthropod community. Non-metric multidimensional scaling (NMDS) analysis revealed that chemical insecticides caused significant shifts in arthropod community structure, whereas biological insecticides preserved community composition similar to the control. Functional group analysis indicated that biological insecticides supported decomposers and natural enemies (predators and parasitoids), while chemical insecticides reduced decomposer proportions and increased specific herbivores such as leafminers. These findings suggest that microbial-based insecticides are more environmentally friendly and effective in maintaining ecological balance within sugarcane agroecosystems. Therefore, integrating biological insecticides into integrated pest management strategies is recommended to promote sustainable and eco-friendly sugarcane cultivation.